Cough peak flow decline rate predicts survival in patients with amyotrophic lateral sclerosis. Issue 2 (4th December 2018) - Matsuda, Chiharu; Shimizu, Toshio; Nakayama, Yuki; Haraguchi, Michiko
ABSTRACT: Introduction : In this study we investigated the prognostic significance of cough peak flow (CPF) decline rate in patients with amyotrophic lateral sclerosis (ALS). Methods : Thirty‐four patients with ALS participated in our investigation. We examined CPF, forced vital capacity (FVC), body mass index, and the revised ALS Functional Rating Scale (ALSFRS‐R), and followed patients to death, tracheostomy, or non‐invasive ventilator dependency. We analyzed the relationship between the rate of decline of each parameter and survival prognosis. Results : The CPF decline rate significantly correlated with the decline rates of the ALSFRS‐R bulbar score ( P  < 0.0001) and FVC ( P  < 0.0001). Patients with a CPF decline rate ≥25% had shorter overall survival ( P  < 0.0001). Cox model multivariate analyses showed that the CPF decline rate was an independent prognostic factor for survival ( P  = 0.021). Discussion: The CPF decline rate reflects the progression of bulbar and respiratory dysfunction and predicts survival. Muscle Nerve 59 :168–173, 2019 Abstract : See editorial on pages 149–151 in this issue .